Just Trauma-Informed Schools: Theoretical Gaps, Practice Considerations and New Directions - Stacy A Gherardi; Myra Garcia; Allison Stoner (International Journal of School Social Work, 2021)
Trauma-informed practices in schools have proliferated over the last decade and are often framed as social justice-oriented practices. This article assesses the theoretical and empirically supported basis for the proposed relationship between trauma-informed practices and social justice. It concludes the current theory of impact linking trauma-informed practices and social justice work is not supported by evidence. In response, we document theoretical gaps which limit the potential reach of trauma-informed practices in responding to social justice issues in schools and identify potential ways in which research and practice can respond to these gaps. We also highlight critical considerations for developing and implementing socially just trauma-sensitive schools, suggesting key questions and steps social workers, educational leaders, and educators can take to embed these considerations in their practice.
Keywords: trauma-informed education; trauma-sensitive schools; trauma-informed practices; social justice; social justice education